2022
DOI: 10.3390/molecules27103076
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Derivative C66 Suppresses Pancreatic Cancer Progression through the Inhibition of JNK-Mediated Inflammation

Abstract: Pancreatic adenocarcinoma is by far the deadliest type of cancer. Inflammation is one of the important risk factors in tumor development. However, it is not yet clear whether deterioration in pancreatic cancer patients is related to inflammation, as well as the underlying mechanism. In addition, JNK is abnormally activated in pancreatic cancer cells and the JNK inhibitor C66 reduces the inflammatory microenvironment in the tumor. Therefore, the aim of this study was to evaluate the role of C66 in the prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…At the same time, BA significantly inhibited the levels of phosphorylated ERK, P38, and JNK in the 3D4/21 cells induced by PCN033 ( Figure 9 ). Our results are consistent with these reports [ 50 , 51 , 52 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…At the same time, BA significantly inhibited the levels of phosphorylated ERK, P38, and JNK in the 3D4/21 cells induced by PCN033 ( Figure 9 ). Our results are consistent with these reports [ 50 , 51 , 52 ].…”
Section: Discussionsupporting
confidence: 94%
“…BA treatment reduced the high phosphorylation levels of c-Jun N-terminal kinase (JNK), p65, p-38, and ERK1/2 triggered by atherosclerosis [ 50 ]. Recent research reported that azelastine inhibited inflammation induced by LPS by inhibiting the JNK/NF- B pathway [ 51 ], and curcumin derivative C66 suppressed inflammation through inhibition of the JNK pathway [ 52 ]. Our results show that BA significantly inhibited the transcription levels of inflammatory factors c-jun and c-fos in the 3D4/21 cells induced by PCN033 ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another curcumin derivative, C66, has good anti-inflammatory activity. C66 was shown to inhibit the progression of PC cells via inhibition of JNK-mediated inflammation [212]. Curcumin inhibits ERK-and JNK-mediated EMT in vitro by upregulating TFPI-2, subsequently suppressing the migration and invasion of PC cells [213].…”
Section: Curcuminmentioning
confidence: 99%
“…Curcumin analogue C66 has been reported to inhibit the proliferation and migration of pancreatic cancer in a dose- and time-dependent manner (25–100 μM, 24–72 h, respectively). Further this analogue could inhibit the inflammatory cytokines (IL-1β, IL-6, IL-8, and IL-15) secretion via the inhibition of JNK pathway ( Chen et al, 2022a ). The anti-pancreatic cancer effects and mechanisms of curcumin and its derivatives are described in detail ( Huang et al, 2022 ).…”
Section: Natural Products Undergoing Clinical Evaluation In Pancreati...mentioning
confidence: 99%